Thermal energy storage enhancement using 3D printed structures in phase change materials - Lum, Leymus Yong Xiang (Nanyang Technological University, 2022)
This project studies and characterises the thermal performance of a topologically optimised heat sink compared to a conventional pin fin heat sink for thermal energy storage applications. The conventional pin fin was designed with similar physical properties such as material, surface area, volume, and base plate size to the optimised fin. The heat sinks were 3D printed using SLM. An experimental setup was also designed and fabricated based on the boundary parameters of the optimised heat sink. The heat sink performances were evaluated by melting two different types of PCMs, RT35 from RUBITHERM and PEG1000 from MERCK. The volume of PCM poured for each heat sink was such that a theoretical PCM height of 50 mm would be formed once the PCM solidifies. The heat sinks were tested under two different heating conditions, viz., constant heat flux (30.64 kW/m2) and constant plate temperature (75˚C). An electrical heater was used to obtain the constant heat flux condition while running water from a water bath through a hot plate produced the constant plate temperature condition for the experiments. Melting visualisation and melt fraction studies were also conducted to capture the melting characteristics and performance of the heat sinks. The experimental results showed that the TO fin has superior melting performance, spreading the heat more uniformly across the device, hence, melting the PCM faster and keeping a more uniform base plate temperature throughout the melting process. The TO fin improved melt times by 19.5% and 9.3% when melting RT35 and PEG1000 under the constant heat flux condition and saw improvements by 16.3% and 9.09% when melting RT35 and PEG1000 under the constant plate temperature condition. However, the TO fin loses out in performance when it comes to keeping a lower base plate temperature than the conventional pin fin design. The TO fin was reported to have a higher base plate temperature of up to 5 K. The experimental results also showed that the PCM's thermal and physical properties played a role in improving the thermal performance of TES devices. The thermal diffusivity of PCMs affected the melt times, while the physical properties such as viscosity affected the base plate temperatures. PEG1000, with a 14% higher thermal diffusivity than RT35, observed melt time improvements by 7.4% and 17.8% using the TO and pin fin designs under the constant heat flux conditions and saw improvements by 17.9% and 24.4% using the TO and pin fin designs under the constant plate temperature conditions. However, as PEG1000 has an estimated 46.3% lower natural convective coefficient, higher base plate temperatures of up to 4 K were reported compared to RT35.